2020
DOI: 10.1002/adma.201906763
|View full text |Cite
|
Sign up to set email alerts
|

Barrierless Free Charge Generation in the High‐Performance PM6:Y6 Bulk Heterojunction Non‐Fullerene Solar Cell

Abstract: Organic solar cells are currently experiencing a second golden age thanks to the development of novel non‐fullerene acceptors (NFAs). Surprisingly, some of these blends exhibit high efficiencies despite a low energy offset at the heterojunction. Herein, free charge generation in the high‐performance blend of the donor polymer PM6 with the NFA Y6 is thoroughly investigated as a function of internal field, temperature and excitation energy. Results show that photocurrent generation is essentially barrierless wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
409
4
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(470 citation statements)
references
References 88 publications
(167 reference statements)
20
409
4
2
Order By: Relevance
“…[11,[25][26][27][28] The PM6:Y6 blend exhibits barrierless free charge generation with low recombination, regardless of excitation energy, rendering it a high-performance binary system. [29] In this work, we incorporated a second donor DRTB-T-C4 into the host PM6:Y6 blend to construct ternary OSCs and obtained a very impressive PCE of 17.13% with a V oc of 0.85 V, a J sc of 24.79 mA cm −2 , and an FF of 0.813. The high PCE is mainly attributed to the enhancement of FF.…”
Section: Doi: 101002/adma202002344mentioning
confidence: 99%
“…[11,[25][26][27][28] The PM6:Y6 blend exhibits barrierless free charge generation with low recombination, regardless of excitation energy, rendering it a high-performance binary system. [29] In this work, we incorporated a second donor DRTB-T-C4 into the host PM6:Y6 blend to construct ternary OSCs and obtained a very impressive PCE of 17.13% with a V oc of 0.85 V, a J sc of 24.79 mA cm −2 , and an FF of 0.813. The high PCE is mainly attributed to the enhancement of FF.…”
Section: Doi: 101002/adma202002344mentioning
confidence: 99%
“…[48] A strong NFA π-π stacking has been reported to enhance charge transport, but not linked systematically with charge generation. [48] Therefore ultrafast spectroscopic studies have shown that charge carriers are also generated efficiently in NFA-based OSCs, [35][36][37][38][39][40] but a detailed photophysical understanding of NFA OSCs still lags behind the continuing, very promising, advances in their device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-dependent J-V measurements, in fact, reveal nearly barrierless free-charge formation and efficient charge generation as low as 100 K. Computational studies on PM6:Y6 show that the A-D-A-D-A molecular architecture of Y6 induces a large quadrupolar moment on a molecular scale, and its dimerization in a unit cell create an electrostatic bias potential able to compensate the coulombic interaction of the CT, therefore enabling barrier-free CT state dissociation (Figure 5d,e). [182] Moreover, the calculation of the Urbach energy extracted from FTPS measurements revealed an E U (26.7 meV) near the thermal energy (kT), indicating low energetic disorder in the system. Charge recombination processes are often associated with the blend microstructure, which is generally investigated by grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements.…”
Section: Pm6:y6-based Solar Cellsmentioning
confidence: 99%
“…Several reports suggest that this blend feature a very high IQE in excess of 95%, which suggests an efficient charge generation and extraction. [182] In fact, a detailed study on these processes using time-delayed collection field and IQE measurements showed negligible losses due to exciton and geminate recombination in a PM6:Y6 blend, the reason of the high FF and J SC in the blend. Contrary to previously reported NFA-based systems, PM6:Y6, together with high FF and J SC , shows an exceptionally high V OC .…”
Section: Pm6:y6-based Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation